The Digital Education based on Public Innovation in Developing a Sustainable Agribusiness Ecosystem - Komarudin, Ilham; Duerawee, Abdulkarim; Santoso, Aris Prio Agus; Lestari, Retna Dewi (CV. Austronesia Akademika, 2025)
This research addresses persistent challenges in Indonesia’s agribusiness sector, including limited access to information, climate change, market fluctuations, and unequal technological adoption. The study aims to design a public innovation model integrating digital education to foster a sustainable agribusiness ecosystem. Employing a qualitative descriptive method, data were obtained through an extensive literature review of scholarly works, policy documents, and reports from international organizations. Thematic analysis and triangulation were applied to identify patterns, challenges, and best practices. The resulting model, Agro-EduHub 5.0, is a community-based hybrid platform linking education, smart farming technology, digital marketing, and multi-stakeholder collaboration. Key features include a hybrid governance model, hyperlocal AI language support, NFT-based incentives, predictive policy dashboards, creative economy villages, agricultural incubators, and CSR-led pilot projects. These innovations address the digital divide, enhance local adaptability, and encourage environmentally friendly practices. The model fosters active participation, cultural relevance, and policy responsiveness, strengthening both resilience and farmer empowerment. It concludes that implementing Agro-EduHub 5.0 through pilot regions and a digital agribusiness consortium will accelerate technology adoption, integrate local wisdom, and promote shared value creation between public and private sectors, ultimately supporting inclusive and sustainable agribusiness transformation.